Corallivory and algal dynamics on some coral reefs in the Persian Gulf - Javid Kavousi; Parviz Tavakoli-Kolour; Sanaz Hazraty-Kari (Global Journal of Ecology - Peertechz Publications, 2020)
Macroalgae are a sign of degradation of coral reefs. Distribution of macroalgae on reefs is moderated by grazers including fish and sea urchins. However, several fish species including certain parrotfishes graze on live coral tissues, at times causing profound damage. In this paper, the potential role of macroalgae in suppressing parrotfish predation on Porites corals, the dominant coral genus in Qeshm Island, is investigated at three research sites at Qeshm Island in the Persian Gulf between April and July 2014 and 2015. Macroalgae, which were abundant in April, decreased significantly in frequency in July, while at the same time, the percentage of Porites colonies, the frequency of fish bite marks on Porites colonies, and the overall area of live coral tissue, which was grazed by parrotfishes increased dramatically, all of which were only negligible in April (with certain exceptions). Nevertheless, no changes were observed in parrotfish abundance. Despite partially supportive statistical data, because of the observed exceptions, this phenomenon is more likely to be due to other factors, in particular the increased nutritional values of the corals in July in comparison to April. However, to understand the cause(s) and mechanisms involved in this annual phenomenon, more investigations seem necessary.